Dyskursywne konstrukcje niepełnosprawności intelektualnej. Krytyczna analiza dyskursu w badaniach nad zjawiskiem niepełnosprawności intelektualnej = Discourse constructions of intellectual disability. A critical analysis of discourse in the research on the phenomenon of intellectual disability - Woynarowska, Agnieszka (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Intellectual disability is a phenomenon focusing the attention of numerous fields of science; biology, medicine, psychology, pedagogy as well as sociology. In the social understanding of intellectual disability, it is viewed as a "social fact", as some social construct. A construct which is being created in the course of social definition, interpretation, granting meaning and changing them, and which depends on both the knowledge and the experiences of a social group. The area of construction and the exchange of meanings is the language and the discourse.
Keywords: niepełnosprawność intelektualna; dyskurs publiczny